On the Organization of Connexin36 Expression in Electrically Coupled Cholinergic V0c Neurons (Partition Cells) in the Spinal Cord and Their C-terminal Innervation of Motoneurons. (1st March 2022) - Recabal-Beyer, A.J.; Senecal, J.M.M.; Senecal, J.E.M.; Lynn, B.D.; Nagy, J.I.
Highlights: Subpopulations of cholinergic V0c neurons in the spinal cord of Cx36 BAC -eGFP mice express eGFP. The eGFP + V0c neurons were identified by their expression of the transcription factor Pitx2. The eGFP + subset of V0c neurons receive dense serotonergic innervation. Evidence suggests that a subset of V0c neurons is coupled by Cx36-containing gap junctions. C-terminals arising from eGFP + V0c neurons preferentially innervate fast vs. slow motoneurons. Abstract: Large cholinergic neurons (V0c neurons; aka, partition cells) in the spinal cord project profusely to motoneurons on which they form C-terminal contacts distinguished by their specialized postsynaptic subsurface cisterns (SSCs). The V0c neurons are known to be rhythmically active during locomotion and release of acetylcholine (ACh) from their terminals is known to modulate the excitability of motoneurons in what appears to be a task-dependent manner. Here, we present evidence that a subpopulation of V0c neurons express the gap junction forming protein connexin36 (Cx36), indicating that they are coupled by electrical synapses. Based on immunofluorescence imaging and the use of Cx36 BAC -enhanced green fluorescent protein (eGFP) mice in which C-terminals immunolabelled for their marker vesicular acetylcholine transporter (vAChT) are also labelled for eGFP, we found a heterogeneous distribution of eGFP + C-terminals on motoneurons at cervical, thoracic and lumber spinal levels. The density of C-terminals on motoneurons varied as did the proportion of those that were eGFP + vs. eGFP − . We present evidence that fast vs. slow motoneurons have a greater abundance of these terminals and fast motoneurons also have the highest density that were eGFP + . Thus, our results indicate that a subpopulation of V0c neurons projects preferentially to fast motoneurons, suggesting that the capacity for synchronous activity conferred by electrical synapses among networks of coupled V0c neurons enhances their dynamic capabilities for synchronous regulation of motoneuron excitability during high muscle force generation. The eGFP + vs. eGFP − V0c neurons were more richly innervated by serotonergic terminals, suggesting their greater propensity for regulation by descending serotonergic systems.